Synthesis of a new Zn-phthalocyanine, photophysical, photochemical, and sono-photochemical properties and DFT studies - Aydogdu, Seyda; Atmaca, Goknur Yasa; Erdogmus, Ali; Hatipoglu, Arzu (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
In recent years cancer has become a global problem and burden to the health system. Photodynamic therapy (PDT) and sonodynamic therapy (SDT) are promising alternatives for cancer treatment. It is very important to use phthalocyanines as sensitizers in such treatments. In this study, a new type of Zn-phthalocyanine compound ( 2 ) peripherally substituted with 4-Hydroxy-7-methoxyquinoline was synthesized and characterized, and its photodynamic and sono-photodynamic efficiencies were examined. Additionally, the electronic and spectroscopic properties of the compounds were calculated theoretically using Density Functional Theory (DFT) and Time-Dependent Density Functional Theory (TD-DFT) methods. The effect of the solvent on the reactivity of the compounds was examined by the Conductive-Like Polarizable Continuum Model (CPCM). The results have indicated that singlet oxygen quantum yield has increased in the sono-photochemical study ( Phi Delta =0.98) compare to the photodynamic study ( Phi Delta =0.70). Experimental and theoretical study results show that the reactivity of the new ligand increases with Zn metal.
Keywords: Phthalocyanine; Sensitizer; Photodynamic therapy; Sono-photodynamic therapy; Density Functional Theory; PHOTOSENSITIZERS; Chemistry; Crystallography